"Cyclical assets" and cyclical capitalization. Issue 2 (6th August 2019) - d'Amato, Maurizio; Siniak, Nikolaj; Mastrodonato, Giulia
Abstract : Purpose: The purpose of this study is providing a possible methodological solution to the valuation of cyclical.assets. International Valuation Standards introduce a brand new definition of property: the cyclical asset (International Valuation Standards Council 2017, IVS 105, p. 39 and p. 41). Among different property valuation methods, normally this kind of properties is appraised using income approach. In this group of methodology, the opinion of value is based on a proportional relationship between property value and rent. In the past years, a group of methods called cyclical capitalization has been proposed (d'Amato, 2003; d'Amato, 2013;d'Amato, 2015; d'Amato, 2017a; d'Amato 2017 b; d'Amato, 2017c). This method proposes an integration between property valuation and property market cycle. Design/methodology/approach: Cyclical capitalization method is applied using a time series of property market rent of offices in prime location in the South Bank area in London. It consists of the determination of more than one all-risk yield to reproduce the property market cycle. Findings: A comparison between the cyclical capitalization and two traditional capitalization rate shows how the proposed model is able to provide a stable opinion of value. Research limitations/implications: The method may represent a contribution for the determination of the value of cyclical assets or for the mortgage lending value. Practical implications: This paper provides the possibility to have a property valuation method less sensitive to upturn and downturn of the property market. Social implications: The valuation based on cyclical capitalization are less sensitive to the upturn and the downturn of the market. Originality/value: It is one of the first scientific paper addressing the problem of the determination of the value of cyclical assets.